Effect of precursor concentration on the electrochemical properties of nickel cobalt phosphate for high-performance electrochromic supercapacitors - Mustafa, Muhammad Norhaffis; Mohd Abdah, Muhammad Amirul Aizat; Numan, Arshid; Sulaiman, Yusran; Walvekar, Rashmi; Khalid, Mohammad (Elsevier, 2023)
This research focuses on developing a high-performance electrode material for sustainable energy applications. The study explores the electrochemical deposition of a nickel-cobalt phosphate composite (NCPC) on a conductive glass substrate. A systematic investigation is conducted to analyze the influence of precursor concentrations, including nickel chloride hexahydrate (NiCl2·6H2O), cobalt chloride hexahydrate (CoCl2·6H2O), and disodium hydrogen phosphate (Na2HPO4), on the electrochromic and energy storage properties of NCPC. Utilizing Design Expert (DoE) software, the optimization process results in a predictive quadratic model with a residual standard error below 5 %, effectively capturing the relationship between independent variables and specific capacitance (Csp). Under optimized conditions (0.1 M NiCl2·6H2O, 0.3 M CoCl2·6H2O, and 0.4 M Na2HPO4), NCPC exhibits remarkable attributes, including a high Csp of 878 F/g (equivalent to 439 mAh/g) for energy storage and an impressive coloration efficiency of 62 cm2/C for electrochromic applications. These exceptional outcomes are attributed to the synergistic effects of NCPC, enhancing electrical conductivity, active site availability, and surface area, collectively contributing to superior electrochemical performance. An electrochromic energy storage device (NCPC//AC) is made, utilizing the optimized NCPC as the positive electrode and activated carbon (AC) as the negative electrode. The NCPC//AC device demonstrates notable performance features, including a high Csp of 135 F/g at a 5 mV/s scan rate, specific power of 750 W/kg, and specific energy of 11 Wh/kg, showcasing an exceptional power-to-weight ratio. Moreover, the NCPC//AC device exhibits excellent stability, retaining 78 % of its capacitance after 5000 charge-discharge cycles, highlighting its durability and long-term viability. In summary, this study emphasizes the exceptional electrochemical properties and performance of the NCPC//AC device, positioning it as a promising sustainable energy technology aligned with SDG 7 of ensuring access to affordable, reliable, sustainable and modern energy for all.